Early life experiences and self-compassion: a structural equation modelling - Satici, S. Ahmet; Uysal, Recept; Akin, Ahmet (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2015)
The aim of the present study is to examine the relationships between early life experiences and self-compassion. Sample of the study consists of 268 university students, in Turkey. Participants completed the Early Life Experiences Scale and the Self-compassion Scale. The relationships between early life experiences and self-compassion were examined using correlation analysis and the hypothesis model was tested through structural equation modeling. In correlation analysis, self-kindness, common humanity and mindfulness factors of self-compassion were found negatively and self-judgment, isolation and over-identification factors of self-compassion were found positively related to early life experiences. The structural model fitted well ((2)=21.92, df=9, (2)/df=2.43, p=.00914, AGFI=.93, GFI=.97, CFI=.98, NFI=.97, NNFI=.95, IFI=.98, RFI=.92, SRMR=.047, RMSEA=.073). According to path analysis results, self-kindness, common humanity and mindfulness were predicted negatively by early life experiences. Further early life experiences predicted self-judgment, isolation and over-identification in a positive way. This research shows that early life experiences have a direct impact on the self-compassion.
Keywords: early life experiences; self-compassion; path analysis; CHILDHOOD; EVENTS; RECALL; SCALE; ABUSE; Psychology